Structural, ferroelectric, and optical properties of Pb0.60Ca0.20Sr0.20TiO3, Pb0.50Ca0.25Sr0.25TiO3 and Pb0.40Ca0.30Sr0.30TiO3 thin films prepared by the chemical solution deposition technique - Pontes, D. S. L.; Pontes, F. M. [UNESP]; Capeli, R. A. [UNESP]; Garzim, M. L. [UNESP]; Chiquito, A. J.; Longo, E. [UNESP] (Elsevier B.V., 2014)
Perovskite ferroelectric Pb0.60Ca0.20Sr0.20TiO3, Pb0.50Ca0.25Sr0.25TiO3 and Pb0.40Ca0.30Sr0.30TiO3, thin films were deposited on Pt/Ti/SiO2/Si and (1 0 0) LaAlO3 substrates by a chemical solution deposition method. XRD revealed the formation of pure thin films on both substrates. All thin films have very flat surfaces, and no droplets were found on their surfaces. Raman data showed a gradual phase transition from tetragonal to a pseudocubic perovskite structure in these thin films; a simultaneous increase in Ca and Sr contents at room temperature was also observed. Temperature-dependent dielectric permittivity measurements revealed a decreasing ferroelectric-to-paraelectric phase transition temperature with increasing Ca and Sr contents. At 100 kHz, ferroelectric-to-paraelectric phase transition temperatures were approximately 505, 355 and 290 K for Pb0.60Ca0.20Sr0.20TiO3, Pb0.50Ca0.25Sr0.25TiO3 and Pb0.40Ca0.30Sr0.30TiO3 thin films, respectively. The E-g of the films were estimated from Tauc's law and were found to be inversely dependent on the Ca and Sr content amounts. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Thin films; Optical transmittance; Chemical synthesis; Phase transition